(untitled) - Seely, John (Oxford, 2013)
The Oxford Guide to Effective Writing & Speaking is the essential guide for everyone who needs to communicate clearly and effectively. It combines practical advice on specific writing and speaking tasks with detailed self-help chapters covering grammar, spelling, and the writing process itself.
Keywords: English language,Ngôn ngữ Anh; Written English,Viết tiếng Anh